American cutaneous leishmaniasis in French Guiana: an epidemiological update and study of environmental risk factors. (16th September 2019) - Loiseau, Rémi; Nabet, Cecile; Simon, Stephane; Ginouves, Marine; Brousse, Paul; Blanchet, Denis; Demar, Magalie; Couppie, Pierre; Blaizot, Romain
Abstract: Background: American cutaneous leishmaniasis (ACL) is endemic in French Guiana. Its epidemiology is evolving, notably because of immigration, anthropization of natural areas, and new microbiological methods . Our first objective was to update epidemiological data. Our second objective was to look for risk factors of ACL. Methods: This multicentric study was conducted from October 2017 to June 2018 in French Guiana. Patients with suspicion of mucocutaneous leishmaniasis were included in case of positive smear, culture, or PCR‐RFLP on skin biopsy . Results: One hundred and twenty‐three patients met the inclusion criteria. Among those patients, 59.3% were Brazilian, mostly gold miners. Most of them (58%) were between 16 and 40 years old, and 69% were male. A large proportion of patients lived in traditional wooden houses (51%). Patients living in coastal towns were usually infected during trips to the primary forest (60%) and had a shorter time to diagnosis than workers of the hinterland. Among environmental risk factors, the presence of a water spring (40%) and dogs around houses (40%) were frequently reported. Leishmania guyanensis represented 80% of cases, followed by Leishmania braziliensis (6%), Leishmania naiffi (2%), and Leishmania amazonensis (1%). Conclusions: Gold mining and trips to the primary forest represent high‐risk situations for ACL in French Guiana, where the population of infected patients is dominated by Brazilian immigrants. Possible environmental risk factors such as the presence of dogs, water sources, and traditional wooden houses require further investigation.